Three Years of the Lightning Imaging Sensor Onboard the International Space Station: Expanded Global Coverage and Enhanced Applications. Issue 16 (19th August 2020) - Blakeslee, Richard J.; Lang, Timothy J.; Koshak, William J.; Buechler, Dennis; Gatlin, Patrick; Mach, Douglas M.; Stano, Geoffrey T.; Virts, Katrina S.; Walker, Thomas Daniel; Cecil, Daniel J.; Ellett, Will; Goodman, Steven J.; et al.
Abstract: The Lightning Imaging Sensor (LIS) was launched to the International Space Station (ISS) in February 2017, detecting optical signatures of lightning with storm‐scale horizontal resolution during both day and night. ISS LIS data are available beginning 1 March 2017. Millisecond timing allows detailed intercalibration and validation with other spaceborne and ground‐based lightning sensors. Initial comparisons with those other sensors suggest flash detection efficiency around 60% (diurnal variability of 51–75%), false alarm rate under 5%, timing accuracy better than 2 ms, and horizontal location accuracy around 3 km. The spatially uniform flash detection capability of ISS LIS from low‐Earth orbit allows assessment of spatially varying flash detection efficiency for other sensors and networks, particularly the Geostationary Lightning Mappers. ISS LIS provides research data suitable for investigations of lightning physics, climatology, thunderstorm processes, and atmospheric composition, as well as real‐time lightning data for operational forecasting and aviation weather interests. ISS LIS enables enrichment and extension of the long‐term global climatology of lightning from space and is the only recent platform that extends the global record to higher latitudes (±55°). The global spatial distribution of lightning from ISS LIS is broadly similar to previous data sets, with globally averaged seasonal/annual flash rates about 5–10% lower. This difference is likely due to reduced flash detection efficiency that will be mitigated in future ISS LIS data processing, as well as the shorter ISS LIS period of record. The expected land/ocean contrast in the diurnal variability of global lightning is also observed. Plain Language Summary: The Lightning Imaging Sensor on the International Space Station (ISS LIS) has been operating on‐orbit since February 2017. The instrument has met all of its major science objectives, including detecting lightning day and night, identifying the specific locations within storms that are producing lightning, millisecond timing accuracy, and high probability of detecting lightning. The instrument also measures energy emitted by lightning, provides background images of storms and their surroundings, and delivers real‐time lightning data. This has enabled enrichment and extension of the long‐term global climatology of lightning from space and provides more recent extension of the global record to higher latitudes (±55°). In addition, the instrument is serving as a standard for comparison to other spaceborne lightning sensors, such as the Geostationary Lightning Mapper (GLM). The real‐time data from ISS LIS have enabled new applications for the benefit of the public, including weather forecasting and public safety. Finally, ISS LIS—in conjunction with other satellite instruments—is providing opportunities for new scientific study in areas such as lightning physics, thunderstorm processes, and atmospheric composition. Key Points: The Lightning Imaging Sensor (LIS) has been providing data from the International Space Station (ISS) since March 2017 ISS LIS provides storm‐scale resolution (4 km) and millisecond timing of global lightning with spatially uniform detection efficiency ( 60%) The 3‐year global lightning climatology is consistent with previous studies (within 5–10%), while extending results to higher latitudes